Paleomagnetism of the Greater Indian passive margin sediments from the Upper Cretaceous succession: Evidence for long-delayed remagnetizations and implication for the India-Asia collision. (15th May 2022) - Xu, Yunchuan; Tan, Xiaodong; Li, Shuai; Li, Yalin; Ran, Bo; Han, Yulin; Sun, Jianping; Ma, Zining
Graphical abstract: Paleomagnetism of the ∼87 Ma Greater Indian passive margin limestones indicates two episodes of prefolding remagnetization, which occurred at ∼11°N (Group A remagnetization) and ∼27°N (Group B remagnetization) paleolatitude positions, and are likely associated with the early Eocene collision between Greater India and an intraoceanic arc subduction system and the early Miocene leucogranite magmatism in the Tethyan Himalaya, respectively. Highlights: Two prefolding remagnetization directions were isolated from upper Coniacian limestones. One was remagnetized at ∼ 11°N during early Eocene India-intraoceanic arc collision. The second was acquired near its present position, associated with magmatism ∼ 20 Ma. A minimum estimate of 610 ± 622 km was yielded for the northern extent of Greater India. Abstract: The Late Cretaceous and Paleogene sediments from the Tethyan Himalaya can provide paleomagnetic constraints on the pre-collision size of Greater India. However, recent studies have shown that these sediments experienced significant chemical remagnetization. To resolve the controversy over the timing of remagnetization, we performed a paleomagnetic study of the Upper Cretaceous (upper Coniacian) Gangbacunkou Formation limestones from Duela, Yadong County in Tibet. A total of 109 cores were collected from three short sections, among which 90 specimens yielded interpretable results. After removal of a scattered remanence at 200–310 °C, linear trajectories were well defined at intermediate to high temperatures up to 400 °C to 500 °C, which fall into two groups of directions. Group A directions are all reversed and inconsistent with the normal polarity of Coniacian sedimentation, indicating a late stage remagnetization; although they passed the inclination-only fold test with an average inclination of − 21.0° ± 5.1° (n = 42, k = 19.5). The in situ Group B directions are distributed around north, with shallow positive or negative inclinations, and the tilt-corrected directions pass the McElhinny fold test. The group A remagnetization event is attributed to an intraoceanic arc–continent collision at 10.9° ± 5.1°N, ∼50 Ma. Previous estimates of the size of Greater India based on data from Gamba and Duela are likely overestimated due to the influence of this collision event. The Group B remagnetization was acquired at 27.4° ± 5.6°N, close to the present latitude, and is likely related to the metamorphism caused by leucogranite intrusion, ∼20 Ma. The latter provides us a minimum estimate of 610 ± 622 km for the northern extent of Greater India.